2017
DOI: 10.1038/nbt.3942
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of B-cell clonal distribution in the human body

Abstract: B cell responses result in clonal expansion, and can occur in a variety of tissues. To define how B cell clones are distributed in the body, we sequenced 933,427 B cell clonal lineages and mapped them to 8 different anatomic compartments in 6 human organ donors. We show that large B cell clones partition into two broad networks—one spans the blood, bone marrow, spleen and lung, while the other is restricted to tissues within the gastrointestinal (GI) tract (jejunum, ileum and colon). Notably, GI tract clones d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
198
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(219 citation statements)
references
References 50 publications
19
198
2
Order By: Relevance
“…A,B) and by measuring percent overlapping clones between the duplicates of each sample, which is expected to be higher if specific clones dominate the specimen (Fig. C) . By both measures, iPALF cases showed significantly increased clonality compared to dPALF and control cases ( P < 0.01).…”
Section: Resultssupporting
confidence: 86%
“…A,B) and by measuring percent overlapping clones between the duplicates of each sample, which is expected to be higher if specific clones dominate the specimen (Fig. C) . By both measures, iPALF cases showed significantly increased clonality compared to dPALF and control cases ( P < 0.01).…”
Section: Resultssupporting
confidence: 86%
“…As extensive sharing of clonotypes among tissues within the gastrointestinal tract has been reported, our results may not be unique to PSC‐IBD, and the expansion of private clonotypes across the gut–liver axis may be a common phenomenon in many disease settings. Paired gut and liver samples from IBD patients without PSC would serve as the ideal control to address this question; however, these patients do not undergo routine liver biopsy or liver transplantation and thus liver samples are not typically available.…”
Section: Discussionmentioning
confidence: 64%
“…It makes teleological sense for PP B cells therefore to be equipped with more robust peripheral tolerance mechanisms, such as the GARP-TGF-β axis. A recent comprehensive study of the B cell clonal distribution in humans revealed two broad clonal networks: one encompassing the blood, bone marrow, spleen, and lungs, and the other that is restricted to tissues within the gastrointestinal tract (75). The group observed that the GI tract clones have higher frequencies of somatic hypermutation, which suggests a biological relevance for the heightened importance for GARP in the PP immune compartment in order to tolerize self and oral antigens.…”
Section: Discussionmentioning
confidence: 99%